Leisure self-care, health and well-being in women's lives. Issue 3 (27th May 2021) - Petty, Lisa; Trussell, Dawn E.
ABSTRACT: Much of the self-care literature originates from the biomedical field and focuses on managing health-deviations. In the social sciences, there has been an increased interest in self-care as a method to promote well-being; yet self-care has not been taken up in the leisure literature. In this article, we examine how 'self-care' is conceptualized across multiple disciplines and advance the concept of leisure self-care. Emphasis is placed on women's lives and the potential for leisure self-care to reproduce, resist, or maintain gender-related ideologies (e.g. femininity, motherhood and caregiving) as well as the need to integrate research within a broad range of theories and perspectives. Finally, we identify future directions for leisure self-care research.